Procedure for the Determination of the Appropriate Protective Foil Size to Reduce Step Voltage Using a FEM Model and Evolutionary Methods - Marko Jesenik; Peter Kitak; Robert Maruša; Janez Ribič (Applied Sciences)
When a fault occurs in a power transmission system, voltages that are dangerous to people may occur. The aim of this work is to present the following method of protection: the use of protective foil installed at the appropriate depth around the transmission pole. Moreover, a procedure is presented for determining the optimal size of the protective film using a minimum number of finite element method calculations. In addition to the finite element method, evolutionary methods are used to determine the appropriate coefficients. Real earthing system data, earth data, and the fault current are obtained from the Slovenian system operator (ELES, d.o.o.) and used exclusively in the presented analyses. The results of determining the appropriate size of the protective foil for two transmission poles are presented, and the determination of the required breakthrough strength of the materials used is shown. The suitability of the proposed method is confirmed. This method is practical and useful when protection with protective foil is required, ensuring only as much as necessary is applied.